Short-Term Outcome of Balloon Angioplasty of Discrete Coarctation of Aorta - Biomy, Reda; Mansour, Heba; Khaliek, EL Said Abdel; Farghaly, HalaEL; Mohamad, Shahira (Cardiology and Cardiovascular Medicine, 2017)
Introduction: Balloon angioplasty has been proposed as a an alternative way to surgery in primary treatment of aortic coarctation(CoA) for both children and infants. Objective: The purpose of this study is to assess the immediate and intermediate term effectiveness and safety of balloon angioplasty in infants and children with native discrete membranous CoA. Patients and methods: Forty consecutive patients with native discrete coarctation of the aorta were treated with balloon angioplasty. They were 8 infants and 32 children; with ages ranged from 2 months to 10 years and all weighted below 35 Kg. All patients were clinically evaluated immediately after and at 6 to 12 months and 18 to 24 months after the procedure. Follow up data were collected and Doppler echocardiography was done before intervention to confirm diagnosis and to plan management and post interventional to follow-up patients and estimate the outcome and complications. Results: Immediate successful relief of native Co A was obtained in 92.5% of the population study, while 7.5% recorded immediate suboptimal results with pressure gradient above 20mmHG. The peak systolic gradient across the coarcted segment was reduced significantly with 82.5% immediately after balloon angioplasty,75% and 73.2% at the end of first and second follow up period respectively. Pressure gradient decreased significantly from 57±15.7 mmHg before balloon angioplasty to 14.23±11.30mmHg 9 to 12 months after, but it was increased slightly to reach 15.15±11.80 mmHg at the end of the second year. The systolic ascending aortic pressure decreased significantly (19%) and the systolic descending aortic pressure increased significantly (11.4%) at the end of the study. Recoarctation occurred in17.5% at the end of the 1st year and balloon angioplasty was repeate